Contemporary trends and challenges in finance : proceedings from the 2nd Wroclaw International Conference in Finance /: proceedings from the 2nd Wroclaw International Conference in Finance. ([2017]) - Jajuga, Krzysztof; Orlowski, Lucjan T; Staehr, Karsten
No abstract available